Striatal Dopaminergic Innervation Regulates Subthalamic Beta-Oscillations and Cortical-Subcortical Coupling during Movements: Preliminary Evidence in Subjects with Parkinson’s Disease - Canessa, Andrea; Pozzi, Nicolò G.; Arnulfo, Gabriele; Brumberg, Joachim; Reich, Martin M.; Pezzoli, Gianni; Ghilardi, Maria F.; Matthies, Cordula; Steigerwald, Frank; Volkmann, Jens; Isaias, Ioannis U. (Frontiers in Human Neuroscience, 2016)
Activation of the basal ganglia has been shown during the preparation and execution of movement. However, the functional interaction of cortical and subcortical brain areas during movement and the relative contribution of dopaminergic striatal innervation remain unclear. We recorded local field potential activity from the subthalamic nucleus and high-density electroencephalography signals in four patients with Parkinson’s disease off dopaminergic medication during a multi-joint motor task performed with their dominant and non-dominant hand. Recordings were performed by means of a fully-implantable deep brain stimulation device at four months after surgery. Three patients also performed a single-photon computed tomography with [123I]N-ω-fluoropropyl-2β-carbomethoxy-3β-(4-iodophenyl)nortropane to assess striatal dopaminergic innervation. Unilateral movement execution led to event-related desynchronization followed by a rebound after movement termination (event-related synchronization) of oscillatory beta activity in the subthalamic nucleus and primary sensorimotor cortex of both hemispheres. Dopamine deficiency directly influenced movement-related beta-modulation, with greater beta-suppression in the most dopamine-depleted hemisphere for both ipsi- and contralateral hand movements. Cortical-subcortical, but not interhemispheric subcortical coherencies were modulated by movement and influenced by striatal dopaminergic innervation, being stronger in the most dopamine-depleted hemisphere. The data are consistent with a role of dopamine in shielding subcortical structures from an excessive cortical entrapment and cross-hemispheric coupling, thus allowing fine-tuning of movement.